2022
DOI: 10.1007/s10639-022-11360-6
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous video-based communication and online learning: an exploration of instructors’ perceptions and experiences

Abstract: Historically, online instructors have primarily, if not solely, used asynchronous text-based communication to interact and communicate with students in online courses. However, despite this use, online instructors and students have expressed concerns and limitations with asynchronous communication. Research suggests that synchronous communication technology may address some of the limitations of asynchronous communication. Further, advances in synchronous video-based communication technology make it easier tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…In synchronous learning contexts, where webcam use has been highly debated, instructors seem to not connect cameras to interaction. This is similar to Belt and Lowenthal's (2023) findings, which indicated camera use was unnecessary for instructor interaction and could introduce its own problems. Trust and Goodman (2023) found that although cameras are beneficial from a social perspective, students have personal reasons for turning them off.…”
Section: Instructor and Peer Interactionsupporting
confidence: 86%
“…In synchronous learning contexts, where webcam use has been highly debated, instructors seem to not connect cameras to interaction. This is similar to Belt and Lowenthal's (2023) findings, which indicated camera use was unnecessary for instructor interaction and could introduce its own problems. Trust and Goodman (2023) found that although cameras are beneficial from a social perspective, students have personal reasons for turning them off.…”
Section: Instructor and Peer Interactionsupporting
confidence: 86%
“…And they could be further used in other situations that require online education (e.g., courses for students in remote areas) [ 114 , 115 ]. However, it should be noted that the effectiveness of educational videos may be different across disciplines [ 116 ]. Hence, education practitioners should adjust the video arrangement based on their situations and the needs of their students.…”
Section: Discussionmentioning
confidence: 99%
“…The VARK model recognizes that learners have diverse preferences and strengths. Tailoring instruction to match these preferences can enhance engagement and understanding (Abutaher, 2017). The importance of this model helps to engage students where they are more likely to be motivated, attentive, and invested in the learning process.…”
Section: Fleming's Vark Modelmentioning
confidence: 99%